Caboclada à libanesa: Experimento Cênico e Memorial Poético de Formação e Criação - CAMPOS, Helane Cibele do Nascimento (2023)
This work is a record of my personal history, my teaching activity and my training in theater, amalgamated in a scenic experiment, Caboclada à Lebanese. The writing of these experiences was configured in my object of study, starting from Durkheim's ideas of collective memory and Walter Benjamim's memory and orality, emphasizing the experience in the construction of knowledge. The poetic construction process had as reference the idea of personal dramaturgy of the actor and life stories, by Wlad Lima, on the influence of the life story in brazilian theater, a contemporary method of theatrical creation. The writing had as a fundamental dialogue the memories, perceptions and poetic analyzes of the researcher and advisor Karine Jansen, in addition to working with the artist-analyst Wlad Lima, who instigated me to write about my place of origin and about the people who allowed me to my constitution, based on the program Heart Spirals, Boiúna dance, used in her Clinics of the Sensitive project. The research, during the graduation in Theater course, helped me to better understand the history of the Lebanese in Pará and the whole story of my riverside family, told throughout this work. This theme was chosen for my research and poetic elaboration because it moves me inside myself and towards the world. It was from my relationship with my father, who was always and still is very present with his knowledge of the world, that I was able to think about existence in a poetic way, animating my soul.